2022
DOI: 10.1007/s42991-022-00268-w
|View full text |Cite
|
Sign up to set email alerts
|

Diverging ecological traits between the Balkan lynx and neighbouring populations as a basis for planning its genetic rescue

Abstract: Selecting appropriate candidates for genetic rescue mostly relies on previous genetic research and monitoring, while ecological and behavioural traits of the remnant and source populations are rarely considered for such conservation measures. Because of their slow recovery, Eurasian lynx Lynx lynx populations in Central and Western Europe have been a repeated target of genetic reinforcements and reintroductions in the past 50 years. Once inhabiting much of south-eastern Europe, the Balkan lynx L. l. balcanicus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…A more challenging case is represented by the Balkan lynx, L. l. balcanicus , whose adaptive differentiation observed in this study is hard to disentangle from the neutral divergence caused by intense genetic drift and prolonged low effective population sizes. Our previous assessment of the Carpathian population as representing the best source of individuals for genetic rescue of this highly endangered population, based on its closest relationship in neutral autosomal variation (Bazzicalupo et al, 2022) and also supported by their ecological similarity (Melovski et al, 2022), could be additionally confirmed by their relative overall adaptive similarity and by their similar environment defined by the most relevant environmental variables.…”
Section: Discussionmentioning
confidence: 82%
“…A more challenging case is represented by the Balkan lynx, L. l. balcanicus , whose adaptive differentiation observed in this study is hard to disentangle from the neutral divergence caused by intense genetic drift and prolonged low effective population sizes. Our previous assessment of the Carpathian population as representing the best source of individuals for genetic rescue of this highly endangered population, based on its closest relationship in neutral autosomal variation (Bazzicalupo et al, 2022) and also supported by their ecological similarity (Melovski et al, 2022), could be additionally confirmed by their relative overall adaptive similarity and by their similar environment defined by the most relevant environmental variables.…”
Section: Discussionmentioning
confidence: 82%
“…The most prominent example of genetic rehabilitation through introducing individuals from another population stems from the Florida panther ( Puma concolor coryi ), where the release of few individuals substantially increased genetic diversity [ 55 ]. Lastly, saving orphans from highly threatened autochthonous populations such as the Balkan one, can contribute towards the recovery of the subspecies and the genetic viability if the release site is carefully planned [ 56 ]. The use of orphan lynx versus wild-caught individuals for the reintroduction and reinforcement projects could mitigate the pressure on vulnerable wild populations that were used as a source until now.…”
Section: Discussionmentioning
confidence: 99%